Metastatic Colorectal Cancer Outcomes by Age Among ARCAD First- and Second-Line Clinical Trials. Issue 2 (26th February 2022) - McCleary, Nadine J; Harmsen, William S; Haakenstad, Ellana; Cleary, James M; Meyerhardt, Jeffrey A; Zalcberg, John; Adams, Richard; Grothey, Axel; Sobrero, Alberto F; Van Cutsem, Eric; Goldberg, Richard M; Peeters, Marc; et al.
Abstract: Background: We evaluated the time to progression (TTP) and survival outcomes of second-line therapy for metastatic colorectal cancer among adults aged 70 years and older compared with younger adults following progression on first-line clinical trials. Methods: Associations between clinical and disease characteristics, time to initial progression, and rate of receipt of second-line therapy were evaluated. TTP and overall survival (OS) were compared between older and younger adults in first- and second-line trials by Cox regression, adjusting for age, sex, Eastern Cooperative Oncology Group Performance Status, number of metastatic sites and presence of metastasis in the lung, liver, or peritoneum. All statistical tests were 2-sided. Results: Older adults comprised 16.4% of patients on first-line trials (870 total older adults aged >70 years; 4419 total younger adults aged ≤70 years, on first-line trials). Older adults and those with Eastern Cooperative Oncology Group Performance Status >0 were less likely to receive second-line therapy than younger adults. Odds of receiving second-line therapy decreased by 11% for each additional decade of life in multivariable analysis (odds ratio = 1.11, 95% confidence interval = 1.02 to 1.21, P = .01). Older and younger adults enrolled in second-line trials experienced similar median TTP and median OS (median TTP = 5.1 vs 5.2 months, respectively; median OS = 11.6 vs 12.4 months, respectively). Conclusions: Older adults were less likely to receive second-line therapy for metastatic colorectal cancer, though we did not observe a statistical difference in survival outcomes vs younger adults following second-line therapy. Further study should examine factors affecting decisions to treat older adults with second-line therapy. Inclusion of geriatric assessment may provide better criteria regarding the risks and benefits of second-line therapy.